A framework to support the development of self-Adaptive service-oriented mobile applications - Passini, William Filisbino [UNESP]; Affonso, Frank José [UNESP] (KSI Research, 2018)
Today's society is increasingly dependent on the use of mobile devices, which have changed over these last 10 years the way people perform their daily tasks. This can certainly be one of the factors that has boosted the demand for development of highquality Mobile Applications (MobApps). In short, to improve the efficiency of the development life cycle, these applications often use third-party components (e.g., software components, web services, and other mobile applications). Service-oriented MobApps have been a feasible alternative to overcome hardware limitations of these devices to increase the processing and storage capacity. In another perspective, it is also noted a change in the behavior of users of MobApps and their needs, which require applications capable of modifying their structure and/or behavior at runtime. Thus, this paper presents a framework to support the development of Self-Adaptive Services-oriented MobApps (Self-MobApps), which enable adaptation of services at runtime. To show the feasibility of our framework, a case study for a smart restaurant was conducted. The results of this study enable us to create a positive perspective on the contribution of our framework to the research communities involved.
Keywords: Framework; Mobile Applications; Service Computing